A theology as big as the city - Bakke, Raymond J. 1938- (Downers Grove, IL IVP, 1997)
Includes bibliographical references.
Keywords: Cities and towns -- Biblical teaching; Cities and towns -- Religious aspects -- Christianity; City churches